Implementing clinical practice guidelines into action : a qualitative study of managing knowledge translation in primary care organisations - Kork, Anna-Aurora; Marttinen, Miia; Laihonen, Harri; Ruusuvuori, Johanna; Ahonen, Juha E.; Kankaanpää, Eila (Biomed central, 2025)
Background Clinical practice guidelines (CPGs) are essential for enhancing healthcare quality and informing evidence-based clinical practices. Despite the availability of strategies, their implementation remains challenging due to the complexities of managing translation CPGs into practice, such as barriers to change, resource limitations and high costs. This study examines management mechanisms that offer valuable insights into how healthcare organizations can manage CPG implementation at the organizational level to optimise high-quality care. Methods This qualitative study examines the management of CPG implementation using interview data (n = 33) from healthcare managers and clinicians in Finnish public primary care. The data were collected through seven focus group interviews across nine public primary care organizations. The interview transcripts were analysed using thematic analysis with a multidisciplinary approach. Results CPGs are considered important tools for improving care quality and promoting shared evidence-based practices. The obstacles to managing implementation included dissemination difficulties, motivation challenges and information overload. Managers and clinicians had contrary views on their roles and responsibilities in CPG implementation. To lead the knowledge translation processes, managers emphasised unit managers’ support, dissemination and communication channels, whereas clinicians viewed CPG implementation as a grassroots effort and the responsibility of each individual. The results illustrate the need for enhancing shared views on CPGs and managing social implementation activities within organizations. Conclusions Successful CPG implementation requires active managerial efforts and clinician dialogue to transform new evidence into locally viable practices. To inform more effective knowledge translation, the five identified management mechanisms included instructions; accountability structures; motivation, goal setting and feedback; communication strategies and participatory practices. In managing CPG implementation, a focus on interaction processes, motivation and feedback is essential for ensuring collective knowledge formation. This study improves the understanding of critical organizational knowledge translation processes by drawing attention to the previously underrepresented managerial aspects in CPG implementation studies. Future researchers, guideline developers, and policymakers should integrate managerial activities and clinician engagement in CPG implementation to ensure effective practices and healthcare quality.
Keywords: Management; Clinical practice guideline; Evidence-based practice; Primary care; Qualitative research; fi=Sosiaali- ja terveyshallintotiede|en=Social and Health Management|